Mental Health Profiles in a Sample of Moroccan High School Students: Comparison Before and During the COVID-19 Pandemic - Mzadi, Abdennour El; Zouini, Btissame; Kerekes, Nóra; Senhaji, Meftaha (Frontiers in Psychiatry, 2022)
Background Given the biological and psychological changes that occur during adolescence, adolescents’ experiences of the COVID-19 pandemic measures could significantly threaten their mental health and cause long-term consequences. Aim This study aims to determine the impact of the COVID-19 pandemic restrictions on the psychological distress of Moroccan adolescents and identify the risk and protective factors that could influence their mental health. Methods The participants in this study were Moroccan high school students who were recruited at two different times—before the COVID-19 pandemic (350 students, mean age: 16.55 years; 53.71% female) and during the COVID-19 pandemic (457 students, mean age: 16.84; 64.1% female). Students responded to the Brief Symptom Inventory and the Godin-Shephard Leisure-Time Physical Activity questionary, and reported information about their psychosocial environment, gender, and age. The scores on the Brief Symptom Inventory dimensions from the pre-pandemic period and during 2020 were compared. A comparison between the scores of the two genders of the 2020 sample was also carried out. In addition, binary regression analysis was performed to predict the associations between gender, frequency of physical activity, the presence of the number of negative psychosocial factors, and those dimensions of the Brief Symptom Inventory that significantly changed between the samples. Results Female students reported higher psychological distress than male students in both data collection periods. During the COVID-19 pandemic, students scored significantly (p < 0.001) higher in depression and paranoid ideation, and they scored significantly (p = 0.01) lower in hostility and anxiety compared with the pre-pandemic period. Female gender and the experience of physical or psychological abuse significantly increased the risk of reporting higher scores in depression and paranoid ideation symptoms during 2020. Moderate and frequent physical activities were significantly and negatively associated with depression (p = 0.003 and p=0.004; respectively). Conclusions This study confirms the stressful impact of the COVID-19 pandemic on Moroccan high school students, who reported more symptoms of depression and paranoid ideation compared with the pre-COVID-19 period. Female students reported higher psychological distress than male students did. The experience of physical /psychological abuse during the pandemic worsened mental health, while moderate/frequent physical activity improved it.